Українська влада на Буковині в листопаді 1918 р.: встановлення, функціонування, причини поразки. (Zaporizhzhia Historical Review, 2021)
The article analyzes the establishment, functioning and causes of Bukovyna Ukrainian authorities’ defeat in November, 1918. It is noted that Ukrainians of the region acted resolutely enough, were rather organized and were able to achieve certain success having seized the authority in their hands. Nevertheless, at the same time there were misleads. First of all, it was the lack of attention given to formation of own armed groups. The belief in solving the political problems peacefully was rather excessive. Therefore, Ukrainian authorities could not resist Romanian armies.